Sustainable development of agriculture and rural areas in the light of programs of strategic development - Adamska, Hanna; Minta, Stanisław (Rozwój zrównoważony rolnictwa i obszarów wiejskich w świetle dokumentów strategicznych, 2017)
One of the key challenges of present agriculture and rural areas is the pursuit of sustainable development. Encompassing enormous resources of a natural nature, rural areas should develop in accordance with the principles of sustainable development so that both current and future generations can benefit of them. Implementing the concept of sustainable development in rural areas is conditional on many factors and requires corrective activities, which is connected with the intervention of the state. The paper analyzes programs and instruments to support agricultural development and rural development in line with the concept of sustainable development at national and local level. Particular attention has been paid to “the Strategy of Lower Silesia Voivodship” and “Strategy for sustainable development of rural, agricultural and fisheries for 2012-2020”
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 491, s. 11-18
Keywords: rural area; agriculture; sustainable development; development strategy; obszary wiejskie; rolnictwo; rozwój zrównoważony; strategia rozwoju